Determinants of smallholder farmers’ responsiveness to agroecological practices and principles in Ethiopia, Kenya and Madagascar - Max Olupot; Oladimeji Idowu Oladele (Department of Sociology, Faculty of Social Sciences, Gorontalo State University, Indonesia, 2027)
Smallholder farmers across East Africa face significant challenges in fully adopting agroecological practices, despite their demonstrated benefits for soil health, biodiversity, water conservation, and farm resilience. This study examined the determinants of smallholder farmers' responsiveness to agroecological principles and practices in Ethiopia, Kenya, and Madagascar using a sample of 993 farmers. A multi-stakeholder cross-sectional survey was conducted using a detailed, structured, and expert-validated questionnaire administered to smallholder farmers, considering multidimensional variation at both the farm and system levels. Multiple regression analysis and Principal Component Analysis (PCA) were employed to explore the underlying dimensions of adoption and predictors of responsiveness. The results revealed substantial variation across countries. In Kenya, farmers implemented 12 or more principles, whereas in Madagascar and Ethiopia, adoption was moderate, with lower uptake of agroecological principles. Farmer Field Schools (FFS) influenced adoption primarily through social learning, whereby farmers collaboratively experiment, observe outcomes, and share experiences, rather than through top-down technology transfer. Regression analysis showed that knowledge co-creation, education level, agroecology-specific land use, and incentives for participation in and sharing of agroecological practices were significant predictors of responsiveness, while structural constraints played a moderating role. These findings highlight the need to prioritize extension models that are inclusive, participatory, and adaptive, linking farmer education, locally appropriate land-use strategies, and targeted incentives to overcome structural barriers and ensure agroecology delivers both ecological resilience and improved livelihoods. PCA extracted seven components—ecological practices, extension methods, social learning, institutional enhancements, experiential knowledge, adoption behaviors, and gender/culture—which explained 63.38% of the total variance. The study concludes that farmers' responsiveness to agroecological principles is shaped by a dynamic interplay of structural, behavioral, and institutional factors. Strengthening participatory extension systems, co-creation platforms, and incentive frameworks can enhance uptake. These findings provide evidence-based insights for designing context-specific interventions to accelerate agroecological transitions towards sustainable agriculture.